A Post-Mortem of Regional Innovation Policy Failure: Scotland's Intermediate Technology Initiative (ITI). Issue 7 (2nd July 2016) - Brown, Ross; Gregson, Geoff; Mason, Colin
Abstract : Brown R., Gregson G. and Mason C. A post-mortem of regional innovation policy failure: Scotland's Intermediate Technology Initiative (ITI), Regional Studies . The Intermediate Technology Initiative (ITI) was one of the most ambitious 'systemic' regional innovation policy instruments developed in the UK in recent years. However, little of the ITI's anticipated outputs materialized and the programme was prematurely terminated. This paper examines the reasons for its failure, which largely centred on the programme's inappropriate design. The findings suggest that greater recognition needs to be given to the specificities of local entrepreneurial ecosystems when designing, aligning and executing systemic innovation policy instruments. It is argued that paying greater attention to policy failures could potentially help innovation scholars better understand how innovation systems function.